Bioinspired Oxidative Cleavage of Aliphatic C–C Bonds Utilizing Aerial Oxygen by Nickel Acireductone Dioxygenase Mimics. Issue 16 (17th April 2019) - Raje, Sakthi; Mani, Kalaikodikumaran; Kandasamy, Parameswaran; Butcher, Ray J.; Angamuthu, Raja
Abstract: Invited for the cover of this issue is Raja Angamuthu from the Indian Institute of Technology Kanpur, India. The cover image shows the oxidative cleavage of aliphatic C–C bonds of the acireductone model substrate bound to the nickel(II) center. The scissors point to the C–C bonds that are cleaved. Abstract : We were excited to find out that the C–C bonds could be broken oxidatively by using aerial oxygen instead of other chemical oxidizing agents … Read more about the story behind the cover in the Cover Profile and about the research itself in theCommunication by R. Angamuthu et al.